O impacto da descentralização das atividades da ANEEL sobre a qualidade da energia elétrica residencial no Brasil - Triandópolis, Alexandre Jorge Oliveira (2009)
One of the objectives of the decentralization of Brazilian Electricity Regulatory Agency - ANEEL’s activities, to the states and to the Federal District, is to make regulatory action approach the agents and consumers, which makes it more agile, more present and adapted to local circumstances. The execution of these activities includes the regulation, the control and the superintendence of services and electrical energy installations in the territory of the respective federal unit, by cooperation agreement with the local regulatory agency. Actually, in Brazil, 85% of the consumers are in the residential section, which means almost 35% of the consumption. This study presents econometric models, with panel data, to measure the effects of decentralization on the quality of electricity distributed in Brazil, in the 2001 – 2007 period. By the same logic, the impacts of education, density (quantity of consumers per Km² of concession) and income on quality, represented by specific indices of ANEEL, are also measured. By examining the results for the estimated models, it is concluded that the decentralization of the activities of ANEEL provides significant effects on services quality when viewed from the perspective of the ANEEL’s Index of Costumer Satisfaction (IASC).